Singular integrals in the Cesàro sense - Bernardis-Medici, Ana Lucía; Martín-Reyes, Francisco Javier (Springer, Birkhäuser Verlag, 2000)
The existence of the singular integral ∫K(x, y)f(y)dy associated to a Calderón-Zygmund kernel where the integral is understood in the principal value sense TF(x)=limε→0+∫|x−y|>εK(x, y)f(y)dy has been well studied. In this paper we study the existence of the above integral in the Cesàro-α sense. More precisely, we study the existence of ...
Keywords: Integrales singulares; Sumabilidad; Singular integrals; Cesáro summability